The nature and structure of the socio-valuable component of valeological direction of future specialists in the field of physical education - Pranova E.V (Kharkov National Pedagogical University, 2013)
We investigated more than 25 scientific and methodological sources of valeological education in vocational education. Reviewed and analyzed the main approaches to structuring components of valeological orientation. The essence of socially-valuable component of valeological orientation of vocational education. The structure of socially-valuable component and described in detail each of its components: values, professional and value orientation and personality components. Given study and determine the presence of each of the above structural components. Formulated specific professional values, which are implemented in valeological of future specialists of physical education. Structured personal component of the socio-valuable component valeological future direction of physical education specialists. The scheme of personal component. It reveals its elements through a system of meaningful and purposeful actions and personality traits that are associated in a logical sequence.